Inhibitors of endoplasmic reticulum alpha-glucosidases potently suppress hepatitis C virus virion assembly and release. - Qu, X; Pan, X; Weidner, J; Yu, W; Alonzi, D; Xu, X; Butters, T; Block, T; Guo, J; Chang, J (2011)
α-Glucosidases I and II are endoplasmic reticulum-resident enzymes that are essential for N-linked glycan processing and subsequent proper folding of glycoproteins. In this report, we first demonstrate that downregulation of the expression of α-glucosidase I, II, or both in Huh7.5 cells by small hairpin RNA technology inhibited the production of hepatitis C virus (HCV). In agreement with the essential role of α-glucosidases in HCV envelope glycoprotein processing and folding, treatment of HCV-infected cells with a panel of imino sugar derivatives, which are competitive inhibitors of α-glucosidases, did not affect intracellular HCV RNA replication and nonstructural protein expression but resulted in the inhibition of glycan processing and subsequent degradation of HCV E2 glycoprotein. As a consequence, HCV virion assembly and secretion were inhibited. In searching for imino sugars with better antiviral activity, we found that a novel imino sugar, PBDNJ0804, had a superior ability to inhibit HCV virion assembly and secretion. In summary, we demonstrated that glucosidases are important host factor-based antiviral targets for HCV infection. The low likelihood of drug-resistant virus emergence and potent antiviral efficacy of the novel glucosidase inhibitor hold promise for its development as a therapeutic agent for the treatment of chronic hepatitis C.